Voorzitter van bouwbond St. Joseph Brouwer (links) met zijn collega van de bouwbond NVV Buijs (midden) - Haas, Joh. de, (1971)
Voorzitter van bouwbond St. Joseph Brouwer (links) met zijn collega van de bouwbond NVV Buijs (midden).